Synthetic fibronectin peptides interrupt inflammatory cell infiltration in transforming growth factor beta 1 knockout mice. - Hines, K L (1994)
Pronounced mononuclear leukocyte (MNL) infiltration occurs in multiple organs of mice homozygous for a transforming growth factor beta 1 (TGF-beta 1) loss-of-function gene mutation [TGF-beta 1 (-/-)], followed by cachexia and eventually death. Consistent with the increased leukocyte adhesion and tissue infiltration, MNLs isolated from spleen, thymus, and peripheral blood of symptomatic TGF-beta 1 (-/-) mice, as compared to littermate controls, exhibited increased adhesion to extracellular matrix proteins and to endothelial cells in vitro. Incubation of TGF-beta 1 (-/-) MNLs with selected synthetic peptides corresponding to cell- and heparin-binding sequences of fibronectin (FN) significantly attenuated adhesion of these cells not only to FN but also to endothelial cells in vitro. Based on these observations, mice were treated with the FN peptides in an attempt to rescue them from tissue inflammation and cardiopulmonary failure. Daily injections of a combination of four synthetic FN peptides that interact with beta 1-integrins and/or cell surface proteoglycans blocked the massive infiltration of MNLs into the heart and lungs of TGF-beta 1 (-/-) mice. Peptide treatment initiated on day 8, coincident with the first evidence of increased leukocyte-endothelial cell interactions, not only blocked tissue infiltration but also moderated the lethal wasting syndrome.